Systematic and taphonomic insights of fossilized feathers: A new occurrence from the Oligocene of Taubaté Basin (SE, Brazil). (December 2016) - Prado, Gustavo M.E.M.; Anelli, Luiz E.; Pacheco, Mírian L.A.F.; Petri, Setembrino; Romero, Guilherme R.
Abstract: Feathers are rare in the fossil record because they have a low fossilization potential. Despite their palaeobiological significance, they also provide important palaeoecological and taphonomic information. Here, we report a new occurrence of three isolated feathers from the shales of the Oligocene Tremembé Formation (Taubaté Basin, SE Brazil). Their possible taxonomic affinities and taphonomic features are also discussed. Analyses identified the specimens as representatives of two pennaceous morphotypes ( i.e., a contour and a rectrice feather). Both are preserved as carbonized traces, although, due taphonomic processes, they show different degrees of preservation. Since the Tremembé Formation is responsible for the most diverse record of Cenozoic birds, and because water-adapted birds ( e.g., anseriformes and phoenicopteriformes) occur in this unit, it is highly possible that these feathers belonged to these aquatic taxa. Further investigations should concentrate on geochemical and microscopic techniques in order to reveal additional taxonomic and paleoecological features currently unknown in Paleogene birds of Brazil. Highlights: We report three fossil feathers of the Tremembé Formation (Oligocene), Brazil. Feathers represent two pennaceous morphotypes – contour and rectrice feathers. Despite represent different morphotypes, both are preserved as carbonized traces. Feathers probably belonged to an aquatic taxa which fossils also occur in this unit. This research open taxonomic and palaeontological questions of Oligocene birds.